2002
DOI: 10.2320/matertrans.43.2855
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Au/SiO<SUB>2</SUB> Nano-Composite Multilayers by Helicon Plasma Sputtering and Their Optical Properties

Abstract: Au/SiO 2 nano-composite multilayers were prepared by helicon plasma sputtering. The Au particles dispersed in the SiO 2 matrix grew with increasing deposition time in the initial time less than 10 s, then changed from network-like to film-like microstructure with increasing deposition time. The optimum deposition time for preparing the Au particles was 8 s, and the size of Au particles was about 6 to 8 nm. The absorption peak due to the surface plasmon resonance of Au particles was observed at the wavelength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In addition, composites based on metal NPs in dielectric matrices prepared by ion-implantation and co-sputtering have raised a significant interest due to their linear and nonlinear optical properties [2,8,23]. Unfortunately, such synthetic approaches do not enable an accurate control of both the concentration and morphology of metal NPs under soft conditions [24][25][26]. A further drawback is the frequent necessity of ex situ thermal treatments, that can be incompatible with the production processes of technological devices [2,8,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, composites based on metal NPs in dielectric matrices prepared by ion-implantation and co-sputtering have raised a significant interest due to their linear and nonlinear optical properties [2,8,23]. Unfortunately, such synthetic approaches do not enable an accurate control of both the concentration and morphology of metal NPs under soft conditions [24][25][26]. A further drawback is the frequent necessity of ex situ thermal treatments, that can be incompatible with the production processes of technological devices [2,8,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy of resonance frequency between the value of theoretical calculation and experimental results may be due to static and dynamic charge transfer [17]. The SPR peak shows a blue-shift trend with the increase of Au content, which is different from that of Au/SiO 2 thin films [18]. It was reported that no obvious change in the peak position was observed between 3vol% and 12vol% Au in Au/SiO 2 thin films, while the resonance peak showed a red-shift trend as the Au content was 12vol%-37vol% and then turned to blue shift by further increasing the Au content from 37vol% to 65vol%.…”
Section: Structure Characterizationmentioning
confidence: 52%
“…The red shift of the SPR peaks with the increasing of metal content and/or with the growing of particle size generally attributes to the quantum size effect of the metal particles. However, the blue shift of the absorption peaks along with the weakening of peak intensities sometimes happens when metal contents are very high, such as the case of Au/SiO 2 films with 37vol% to 65vol% Au [18], which is related to the partial connection of metal particles. In the present study, all samples show the blue shift of absorption peaks regardless of Au content, and their peak intensities also keep a high level even for the 45.2wt % and 60.5wt% Au dispersed films.…”
Section: Structure Characterizationmentioning
confidence: 96%
“…Figure 2 shows the XRD patterns of the as-deposited Au/ SiO 2 film containing 37 vol% Au and those heat treated at 700 and 900 C for 1 h. In the as-deposited film (a), since the mean diameter of Au particle was less than 8 nm, 17) no diffraction peak was observed except the typical halo pattern of SiO 2 glass around 22…”
Section: Resultsmentioning
confidence: 99%
“…The mean diameter of Au particles in the as-deposited films was always less than 8 nm regardless of the Au content, and the films containing the Au content less than 12 vol% showed a layer-by-layer structure. 17) The increase in Au content reduced the distance between the Au layers, i.e., the thickness of SiO 2 layer. For the as-deposited Au/SiO 2 film containing 5 to 10 vol% Au, there should be no change of the absorption peak positions, and the intensity of the absorption peak would increase with increasing Au content.…”
Section: Resultsmentioning
confidence: 99%